Developmental roles and molecular characterization of a Drosophila homologue of Arabidopsis Argonaute1, the founder of a novel gene superfamily. - Kataoka, Y.; Takeichi, M.; Uemura, T. (Genes to cells : devoted to molecular & cellular mechanisms, 2001)
Arabidopsis Argonaute1 (AGO1) is the founder of a novel gene superfamily that is conserved from fission yeasts to humans. AGO1, and several other members of this superfamily are necessary for stem cell renewal or RNA interference. However, little has been reported about their roles in animal development or about the molecular activities of any of the members.We have isolated a Drosophila homologue of AGO1, dAGO1, in our attempt to search genetically for regulators of Wingless (Wg) signal transduction. dAGO1 is broadly expressed in the embryo and the imaginal disc. dAGO1 over-expression at wing margins suggested that it behaves as a positive regulator in the genetic background employed. Loss-of-function mutations of dAGO1, unexpectedly, did not give typical segment polarity phenotypes of the wg class; instead, dAGO1 maternal and zygotic mutant embryos showed developmental defects, with malformation of the nervous system being the most prominent. The mutant decreased in the numbers of several types of neurones and glia examined. The dAGO1 protein was distributed in the cytoplasm and co-sedimented with poly(U)- or poly(A)-conjugated beads.Our results suggest that the dAGO1 protein exerts its developmental functions by binding to RNA either directly or indirectly.